Effect of mangrove crab soup extract on dengue virus serotype-2, platelet cell activity and U937 human monocyte cancer cell line - Zahir, Nurul Nadiah Mad (Pusat Pengajian Sains Kesihatan, 2014)
Dengue is a major mosquito-borne disease in Malaysia. Currently, there is no effective antiviral therapy or approved vaccine available for dengue infection. Its infection is responsible in the drastic decrease of platelet count or thrombocytopenia. Therefore, finding the alternative therapeutic medicine is important. One of the popular traditional remedy to treat dengue infection in Malaysia is by taking a mangrove crab soup. It has been proven in-vivo to increase the platelet count of dengue patient. However there is no in-vitro study conducted on the effect of this crab soup on dengue virus and platelet count. Therefore, this study was carried out to investigate the effect of mangrove crab soup extract on the dengue virus serotype-2 (DENV-2), platelet cell activity and cytotoxicity on U937 human monocyte cancer cell line. The cytotoxicity assay was performed to estimate the maximum non-toxic dose (MNTD) of mangrove crab soup extract on U937 human monocyte cell line before using in the in vitro antiviral assay treatment. After the treatment, reverse transcriptase PCR was performed to screen the presence of specific gene of /?-actin of U937 cells, DENV-2 and platelet factor-4. Antiviral effect of this crab soup was also determined by quantifying the DENV-2 RNA copy numbers based on Ct value using reverse transcriptase-qPCR (RT-qPCR) and the data was analysed by using one-way ANOVA test. Due to the presence of non-specific bands on the agarose gel electrophoresis in some of the samples, the platelet cell activity cannot be further quantified by RT-qPCR. The non-specific bands were sent for sequencing and the sequence was blasted with the reference sequences from NCBI GenBank. The result reveals that it was 45S pre-ribosomal RNA (45S pre-rRNA) derived from U937 human monocyte cancer cell line. In overall, the result of this study shows that although this crab soup has no significant inhibitory effect on DENV-2 and a minor cytotoxic effect on U937 cells, but it has an encouraging effect in increasing the platelet activity and inhibitory of 45S pre-rRNA of U937 human monocyte cancer cell line. Thus, this crab soup need to be further investigated to discover its potential as an anti-tumour agent.